Response of Some Blood Immune System Variables After Two Different Aerobic Efforts for Long Distances Runners - Hana, Shatha Hazim Gorgees (Holistic Journal of Sport Education, 2026)
Aim of current study is to know importance of differences in values of pre-tests of two aerobic exercises Sharki and Bruce on some blood immune system variables for long distances runners, know importance of differences in values of post-tests of two aerobic exercises Sharki and Bruce on some blood immune system variables for long distances runners. Researcher hypothesized no morally significant differences are found in values of pre-post tests of two aerobic exercises Sharki and Bruce on some blood immune system variables for long distances runners. Researcher used descriptive method due to its appropriateness. Society was 10 advanced players of Nineveh governorate for medium and long distances the sample were 6 long distances players representing 60% chosen randomly chosen . the following statistical means were used t-test for related samples, standard deviation, means, variance factor. Researcher founded two aerobic exercises made moral change in WBC , MON , GRA Glubiolin, two aerobic exercises didn’t make moral change in LYM variables, means of aerobic exercise Sharki was higher than that of Bruce. Recommended necessity of periodical check for athletes in specialized athletic centers to know health status of athletes in general and immune system in particular to study same variables on female athletes. Make a comparative study between male and female athletes regarding same variables and same and exercises